THE FACTORS OF NATURAL TOURISTS FOR BATU KATAK IN BATUJONGJONG VILLAGE, BAHOROK, DISTRICT IN LANGKAT REGENCY - Anggia Ramadhan; Ahmad Fadlan; Nurul Nabila Utami (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to determine and analyze the influence of tourism promotion, tourist attractions, tourist facilities, accessibility, service quality, accommodation, tourist age, and tourist income in Batu Katak Tourism Object, Batujonjong Village, Bahorok District, Langkat Regency. This study used primary data collected to see the classification of tourist visit levels using a sample of 90 visitors to tourist attractions, using the Confirmatory Factor Analysis (CFA) analysis method and then using Multiple Linear Regression. The results of the study showed that of the 8 variables analyzed using a factor analysis model that affects the level of tourist visits to Batu Katak, only 3 factors affect the level of tourist visits, namely tourism promotion, service quality, and tourist income. Based on the results of multiple linear regression analysis, it shows that tourism promotion and service quality have an effect and are signed on the factors of Batu Katak tourism visitation rates, while tourist income has an effect and is not significant on the level of tourist visits to Batu Katak Batujongjong Village, Bahorok District, Langkat Regency.